2011
DOI: 10.1039/c0np00049c
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action and biosynthesis of the azabicycle-containing natural products azinomycin and ficellomycin

Abstract: Only a handful of aziridine-containing natural products have been identified out of the more than 100,000 natural products characterized to date. Among this class of compounds, only the azinomycins (azinomycin A and B) and ficellomycin contain an unusual 1-azabicyclo[3.1.0]hexane ring system, which has been reported to be the reason for theDNAcrosslinking abilities and cytotoxicity of these metabolites. Both families of natural products are produced by Streptomyces species, Streptomyces sahachiroi and Streptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…3,19 In vivo experiments on this PKS have suggested that AziB alone is responsible and sufficient for the biosynthesis of 5-methylnaphthoate. 20 The AziB protein was successfully cloned and overexpressed in E. coli giving a 187 kDa His-tagged apo -enzyme form of the PKS that was successfully purified by Ni-NTA chromatography (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…3,19 In vivo experiments on this PKS have suggested that AziB alone is responsible and sufficient for the biosynthesis of 5-methylnaphthoate. 20 The AziB protein was successfully cloned and overexpressed in E. coli giving a 187 kDa His-tagged apo -enzyme form of the PKS that was successfully purified by Ni-NTA chromatography (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…3 In an early phase clinical investigation, azinomycin B has shown favorable results against 36 cases of malignant neoplasms, with the most promising effects observed against squamous cell carcinoma. 4 In vitro studies suggest their biological activity resides in their ability to cross-link double stranded DNA through the actions of the electrophilic aziridine and epoxide moieties of the molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have carried out a functional knockout of aziA2 within the azinomycin gene cluster of Streptomyces sahachiroi [1112]. The gene encodes a NRPS (non-ribosomal peptide synthetase, an enzyme involved in the biosynthesis of various peptide containing secondary metabolites) module of unusual domain architecture consisting of condensation, peptidyl carrier protein, and condensation domains (C-PCP-C), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, azinomycin B (carzinophilin) is a complex natural product isolated from Streptomyces sahachiroi that contains densely assembled functionalities and has potent antitumor activity due to DNA intercalation and interstrand cross-linking ( Figure 5.25). 57,58 It was used with some success in a clinical study in humans with several types of cancer.…”
Section: Epoxidesmentioning
confidence: 99%